Rapid Identification of Triphenylmethane Dyes by Ion Mobility Time-of-Flight Mass Spectrometry. Issue 6 (December 2016) - Sysoev, Alexey A.; Poteshin, Sergey S.; Chernyshev, Denis M.; Sysoev, Alexander A.
An ion mobility time-of-flight mass spectrometry (IM-TOFMS)-based method has been preliminarily investigated for the identification of triphenylmethane ballpoint pen dyes on paper. The dyes were sampled from one-year-old ballpoint pen ink entries. The entries were written on paper documents stored in the dark in a bookcase. Sample solutions were prepared by extraction of dyes in a vial. Basic violet 2, Methyl violet 6B, Methyl violet 2B and Crystal violet were characterized by IM-TOFMS. Since the ballpoint ink dyes contain ionic compounds, the studied compounds were expected to form stable peaks in the atmospheric pressure drift tube ion mobility spectrometry, and this was experimentally verified. The studied dyes produce [M – Cl] + ions in electrospray and form stable individual mass-selective reduced mobility peaks. The values of the characteristic reduced mobility are: 1.187 cm 2 /(V·s) for Basic violet 2 ( m / z 330.20), 1.165 cm 2 /(V·s) for Methyl violet 6B ( m / z 344.21), 1.156 cm 2 /(V·s) for Methyl violet 2B ( m / z 358.23), 1.123 cm 2 /(V·s) for Crystal violet ( m / z 372.24). IM-TOFMS is expected to be a promising tool for fast and reliable analysis of dyes in complex matrixes.